A New Facile Route to Flexible and Semi‐Transparent Electrodes Based on Water Exfoliated Graphene and their Single‐Electrode Triboelectric Nanogenerator. Issue 39 (23rd August 2018) - Shin, Dong‐Wook; Barnes, Matthew D.; Walsh, Kieran; Dimov, Dimitar; Tian, Peng; Neves, Ana I. S.; Wright, C. David; Yu, Seong Man; Yoo, Ji‐Beom; Russo, Saverio; Craciun, Monica F.
Abstract: Wearable technologies are driving current research efforts to self‐powered electronics, for which novel high‐performance materials such as graphene and low‐cost fabrication processes are highly sought.The integration of high‐quality graphene films obtained from scalable water processing approaches in emerging applications for flexible and wearable electronics is demonstrated. A novel method for the assembly of shear exfoliated graphene in water, comprising a direct transfer process assisted by evaporation of isopropyl alcohol is developed. It is shown that graphene films can be easily transferred to any target substrate such as paper, flexible polymeric sheets and fibers, glass, and Si substrates. By combining graphene as the electrode and poly(dimethylsiloxane) as the active layer, a flexible and semi‐transparent triboelectric nanogenerator (TENG) is demonstrated for harvesting energy. The results constitute a new step toward the realization of energy harvesting devices that could be integrated with a wide range of wearable and flexible technologies, and opens new possibilities for the use of TENGs in many applications such as electronic skin and wearable electronics. Abstract : Shear‐exfoliated graphene integrated into a flexible and semitransparent triboelectric nanogenerator is developed by using a new facile isopropyl‐alcohol‐assisted direct transfer method. Environmentally and industrially preferred graphene solutions in water are obtained by shear exfoliation. Their graphene flakes are transferred onto any substrate, including poly(ethylene terephthalate), paper, fibers, glass, and SiO2 /Si, driven by the transition of ispropyl alcohol liquid to vapor.